Avaliação dos parâmetros de insensibilização e os impactos na qualidade da carne de perus (Meleagris gallopavo) - Parteca, Sandro (2016)
Brazil is the third largest producer and exporter of turkey meat, especially in Paraná state, with the largest production volume. In worldwide the animal welfare is a prerequisite for food quality of animal origin, especially in Europe. The Regulation of European Community No 1099/2009 provides requirements for poultry stunning that associate with animal welfare as a means to minimize the pain and suffering from the slaughter. Improper application of callousness should produce low-quality meat, and significant industry losses. This Research aimed to evaluate the impacts on the quality of meat from turkeys, applying electrical stunning parameters established in the Regulation No 1099/2009 of the Council of 24 September 2009. Was applied an outline with 8 tests set equidistantly to frequency, and set parameters for current and voltage, and a control test. Were conducted qualitative assessments of hematoms and bruises / fractures in carcasses, hematoms, blood splashed and bleeding in turkey breast, and quantitative pH, color (L *), water holding capacity and shear force in turkey breast. The individual assessments showed no significant difference (p>0,05). In multivariate cluster analysis was the formation of two distinct groups: group 1 - 50 Hz to 200 Hz (low frequency) and group 2 - 633 Hz to 1500 Hz (high frequency), which showed significant difference (p= 0,016). In principal component analysis multivariate, the group 1 tend to have a higher incidence of bruising, blood splashed, bleeding and water holding capacity in breast turkeys, and bruises / fractures and hematoms on carcasses. The Group 2 tends to have a lower incidence of these parameters, and higher pH values, shear force and color (L *). Positive correlation was obtained for the parameters pH and shear force (r= 0.7506, p=0.0198); bleeding and splashed blood (r= 0.8811, p= 0.0017), and negative correlation to color (L*) and splashed blood on breast (r= -0.7889; p= 0.0115); breast hematoms and shear force (r= -0.7844; p= 0.0123). It has been observed that at lower frequencies stunning tends to have higher incidence of defects in the carcasses and turkey breast. The use of high frequencies in stunning, create smaller quantity of trimming, and an increase in turkey breast volume produced, with a financial gain of approximately R$250,000.00 / year. Moreover, there is no need increase the workers to do the trimming tasks and, therefore, higher financial results for companies. Therefore, we recommend the use of high frequencies in the stunning of turkeys.